Senyawa Music Exploration In The “Membaladakan Keselamatan” Album - Dadang Dwi Septiyan; Wadiyo Wadiyo; Slamet Haryono; Yudi Sukmayadi (Universitas Negeri Semarang, 2022)
Abstrak. Senyawa is a place for sound experimentation by two of its personnel, namely Rully Shabara and Wukir Suryadi. Senyawa fans always look forward to exploration, both in every show and in every album. This study aims to identify, analyze, and describe the musical exploration carried out by Senyawa in the Membaladakan Keselamatan album. The research method used is a qualitative method. The focus in this research is the description of the exploration practices carried out by the two Senyawa personnel in the Membaladakan Keselamatan Album. Based on the results of the study, it was obtained data that in the making of the Membaladakan Keselamatan Album a plan was not carried out, but only the result of practice behavior that occurred organically. However, even though Senyawa is an experimental musical group, for Senyawa, practice is the most important thing in a creative process. Especially in the Membaladakan Keselamatan Album, this album is a very experimental album for Senyawa, because making normal songs as usual for Senyawa is something out of the ordinary. Especially in the Membaladakan Keselamatan Album, Senyawa is challenged in the genre that is presented, namely Ballads. The vocal and acoustic guitar explorations in the Membaladakan Keselamatan Album seem simple but the purpose of this album is to reinforce the public's definition of Senyawa, especially to appreciators who often define the strangeness of Senyawa exploration as well as with the use of obscure lyrics. The implication of this research is to provide information about the importance of independence in working in order to become a more complete entity.